The Role of Organizational Identification on Employee Well-Being in Human Resource Practices - Indrayanti (ANIMA Indonesian Psychological Journal, 2013)
The aim of this study was to investigate the role of organizational identification (OI) on employee well-being (WB). Human resource practice (HRP) was predicted as the moderator of the correlation between OI and WB. Employees of public and private sectors (N = 310) completed three questonnaires on OI, WB, and HRP, which were confirmed to be reliable through reliability analysis. Data analysis showed a significant correlation between OI and WB (r = .699; p < .01). As expected in the hypothesis, HRP was the significant moderator on the correlation between OI and WB, with the F value change of 46.485; p < .01 and the Adjusted R 2 from .486 to .552. Studi ini bertujuan untuk mengetahui peran identifikasi organisasi (IO) terhadap wellbeing pada karyawan (WB). Praktek Sumber Daya Manusia (PSDM) diprediksi sebagai moderator dalam hubungan antara IO dan WB. Sejumlah 310 responden yang berasal dari karyawan sektor publik diminta untuk mengisi tiga buah kuesioner yakni IO, WB, dan PSDM. Hasil analisis reliabilitas alat ukur menunjukkan ketiga instrumen tersebut reliabel untuk digunakan dalam penelitian ini. .Analisis data menunjukkan adanya hubungan yang sangat signifikan antara IO dan WB dimana r= .699; p < .01. Seperti yang telah diduga sebelumnya, PSDM secara sangat signifikan menjadi moderator dalam hubungan antara IO dan WB dengan perubahan nilai F sebesar 46.485; p< .01 dan Adjusted R 2 bergerak dari .486 menjadi .552.